TINJAUAN PELAKSANAAN PIDANA PENJARA TERHADAP KETERPADUAN DENGAN TUJUAN PEMASYARAKATAN - Agustina, Sakinah; Yusi, Suryani (Fakultas Hukum Universitas IBA Palembang, 2023)
Abstract Imprisonment as the main punishment is the punishment that is most threatened against the perpetrators of crimes. This is one of the causes of over-capacity and imprisonment in prisons which affects the process of fostering convicts in achieving correctional goals. As an effort to overcome this, the government uses moderate steps by bringing up alternative punishments besides imprisonment, namely supervision and social work which are accommodated in the new Criminal Code, and to realize integration with the goals of correctional, revisions are made to the Correctional Law No. 12/1995 to become Law No. 22/2022 .